Problematic internet use profiles and psychosocial risk among adolescents. - Halley M Pontes (Public Library of Science (PLoS), 2021)
Objective Although Problematic Internet Use (PIU) is an emerging area of study in psychology, little is known about the unique features of specific subgroups of internet users and their psychosocial vulnerabilities within robust and nationwide populations. Methods The aim of this study was to identify distinct latent groups of internet users based on their PIU risk and to compare their psychosocial outcomes. To achieve this, a nationally representative sample of adolescents of the same grade (N = 1,066, Meanage = 13.46 years, range = 12-16) was recruited from several schools in Slovenia through stratified random sampling. Results A Latent Profile Analysis (LPA) revealed a two-class solution, with Class 1 (n = 853, 80%) featuring 'low PIU risk' participants and Class 2 (n = 213, 20%) including 'high PIU risk' participants. Behaviorally, the main feature of Class 1 denoted 'time management difficulties' while Class 2 was best characterized by 'mood and time management issues'. Further frequentist and Bayesian analyses indicated that Class 2 presented greater psychosocial risk compared to Class 1 due to significantly higher levels of PIU (generalized and across specific PIU subfactors) coupled with lower levels of subjective well-being and self-control. Conclusions Contrary to what was initially envisaged, the two classes did not differ in terms of perceived quality in parent-child relationship. This study shows that PIU patterns and symptom-severity may be developmentally specific, further highlighting the need for clinically age-adjusted PIU screening practices within epidemiological and healthcare settings.